Regional Disparities in Urban Population Access to Sanitation Services. Case Study: Romania - Mihai, Florin; lamasanu, Andreea; Apostol, Liviu (Richtmann Publishing, 2012)
Sanitation services still not fully cover the urban population and this leads to different types of pollution and affects the urbanlandscape. This paper aims a geographical approach by highlighting territorial disparities in the Romanian counties regarding the urbanpopulation access to waste collection services and to examine the environmental issues. Statistical database processed by ascendinghierarchical cluster analysis are mapped at the level of Romanian counties achieving a spatial-temporal analysis for the period 2003-2008. The paper also discuss about the current dysfunctions existing in urban waste management from Romania. Development of wastemanagement facilities are in the process of transition from a traditional system based only on landfilling towards an integrated wastemanagement system which develops the recycling and recovery of waste generated. Romania as an EU member country must improvethe quality of sanitation services. Each city must provide the full collection of municipal waste generated in order to eliminate the illegaldumping.